NILAI RETENSI NITROGEN DAN ENERGI METABOLIS BROILER YANG DIBERI RANSUM TEPUNG LIMBAH SAWI PUTIH (Brassica rapa L. subsp. pekinensis) - The, Fransisca; Mandey, J S; Kowel, Y H.S; Regar, M N (Universitas Sam Ratulangi, 2017)
ABSTRACT THE VALUE OF NITROGEN RETENTION AND METABOLIZABLE ENERGY OF BROILER DIETS WITH MUSTARD MEAL (Brassica rapa L. subsp. pekinensis) This research was conducted Â to determine the value of nitrogen retention (NR) and nitrogen corrected metabolizable energy value (AMEn) of broiler diets containing waste of mustard meal. Research used 18 MB 202 of broiler chickens 6 weeks of age that consists of 3 days of preliminary and 3 days collecting data. The experimental wasdesigned by a completely randomized design (CRD), which consists of 3 treatments and 6 replications. The treatmentswere: R0 = 100% based diet (BD) + 0% mustard waste meal (MWM), R1 = 90% BD + 10% MWM, and R2 = 80% BD + 20% MWM. Variables were nitrogen retention (NR) and metabolizable energy Â nitrogen corrected (AMEN) value. Results showed that the NR value was significantly (P <0.05) affected by treatments and the AMEn was highly significant (P <0.01) affected by treatments. HSD test showed thatthe NR value of R1(54,59%) and R2 Â (41,71%) was significantly decreased compared to control (41,71%).The AMEn value oftreatment R1 (2504.07 Kcal/kg) and R2 (2117.00Kcal/kg) was signicantly decreased compared to R0 (3141.57 Kcal/kg). Based on the NR and AMEn values, it can be concluded that mustard waste could be used up to 10% in dietof broilers Keywords : broiler, metabolizable energy,mustard, nitrogen retention,